Social Media Sentimental Analysis using Machine Learning - Mr. Manoj K, Ms. Akhila R, Mr. Ganesh M, Mr. Parikshith Nayaka S K (International Journal of Advanced Science and Technology, 2020)
Machine learning is a powerful technology which has the ability to turn information into knowledge. Even in our daily life we use machine learning a lot, like even we google something or to detect cancer or even for most of the automated works also. Machine Learning helped us like to convert the data the we’ve collected into some useful information or feedback that will be a lot helpful for companies to develop a product or to come over their drawbacks. Our goal is needed in the project to create a sentiment classifier. This happened by the help of high-level deep learning framework and other NLP libraries, we have built and conducted several experiments, including pre-processing of documents, Representation and simulation of texts of classifiers. In this paper, we’re going to show a detailed review of Twitter data set sentiment analysis and clarify what we have done to achieve a classifier of emotions. Keywords: Machine Learning, Natural Language Processing, Python, Sentimental Analysis.